Переописание паразитического перепончатокрылого Neochrysocharis immaculata (Hymenoptera, Eulophidae) — паразита шведской мухи - Рябчинский, А.В.; Тряпицын, В.А. (Вестник зоологии, 1984)
A Redescription of a Parasitic Hymenopteran, Neochrysocharis immaculata (Hymenoptera, Eulophidae), a Parasite of the Frit Fly. Ryabshinsky A. V., Triapitzin V. A.—
Vestn. zool., 1984 No 1. Redescription of the type-series of Neochrysocharis immaculate
Kurdjumov, 1912, reared from puparia of the Frit Fly in Poltava district (Ukraine),
with lectotype designation. The species is resurrected from synonymy of N. araius
(Walker, 1838), described from England.